Studies on stability parameters and sustainability index for selecting stable genotypes in Asiatic cotton (Gossypium arboreum) - VERMA, S K; TUTEJA, O P; MONGA, D (The Indian Journal of Agricultural Sciences, 2026)
Comparative studies on stability parameters and sustainability index for selecting stable genotypes in Asiatic cotton (Gossypium arboreum L.) was carried out according to Eberhart and Russell model with sustainability index model. Stability analysis was carried out on seven Gossypium arboreum genotypes for seed cotton yield, seed index, lint index, number of bolls/plant, boll weight, GOT, 2.5% span length, micronaire and bundle strength on three years data, viz. 2004, 2005 and 2006. Based on the linear component (bi), non-linear response (S2di) and high mean performance (x), the genotypes LD 861 and CISA 614 were found stable for seed cotton yield. While based on sustainability index and best performance, the only genotype CISA 614 was found to be stable. For other traits like seed index, lint index, GOT, no. of bolls/plant, boll weight and micronaire, the deviation from regression was non-significant and on the basis of sustainability index, the variety CISA 614 was found stable having sustainability index more than 80%. For seed index, GOT, micronaire, 2.5% staple length, bundle strength, all the genotypes recorded very high sustainability index, which indicated that these characters are least influenced by the environmental factors, however, the genotype CISA 614 has high sustainability index for 2.5% span length, whereas very high sustainability index was expected. For many characters the results were found in conformity based on Eberhart and Russell model and hence the sustainability index model may be used for selecting the stable genotypes, however for 2.5% staple length it was found contrary.